Formulasi, Uji Stabilitas Fisik dan Aktivitas Antioksidan Krim Ekstrak Etanol Biji Nangka (Artocarpus heterophyllus L.) - Siti Muliani Julianty; Syarifah Nadia; Azkia Putri Ramud (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
Jackfruit seeds (Artocarpus heterophyllus L.) contain secondary metabolites—such as flavonoids, tannins, saponins, alkaloids, and steroids/terpenoids—that possess potential as natural antioxidants. This study aimed to evaluate the effect of adding jackfruit seed ethanolic extract on the physical characteristics and antioxidant activity of cream formulations. Creams were formulated with extract concentrations of 0%, 2.5%, 5%, 7.5%, and 10%. Evaluations included phytochemical screening, organoleptic assessment, homogeneity, pH, spreadability, viscosity, irritation testing, and antioxidant activity analysis using the DPPH method. Phytochemical screening confirmed the presence of flavonoids, alkaloids, saponins, tannins, and steroids/terpenoids in the extract. All formulations produced homogeneous, non-irritating creams with pH, ​​spreadability, and viscosity values ​​that met the physical quality standards for topical preparations. Antioxidant activity increased with higher extract concentrations, evidenced by a decrease in IC50 values ​​from 101.13 µg/mL (FI) to 47.84 µg/mL (FV). Based on antioxidant activity classification, formula FV (10%) fell into the very strong category (IC50 < 50 µg/mL), while the other formulas ranged from moderate to strong. The results demonstrate that the addition of jackfruit seed ethanolic extract enhances antioxidant activity without compromising optimal physical quality, as it achieves a balance between antioxidant efficacy and physical characteristics that meet required standards.